Immunocyte lipid metabolic reprogramming: a novel pathway for targeted intervention in autoimmune diseases - Cui, Yanyu; Feng, Zhendong; Zhao, Qihan; Dai, Haoran; Zheng, Yang; Rui, Hongliang; Liu, Baoli (Frontiers in Immunology, 2025)
Lipids orchestrate immune signaling beyond structure and energy. In autoimmune diseases (ADs), immune cells rewire fatty-acid and cholesterol pathways under microenvironmental pressures, creating pharmacologically actionable dependencies. This metabolic dysregulation is not merely a passive consequence of immune activation but is a key driver of disease progression. This review synthesizes evidence from human and preclinical studies to systematically outline the core regulatory networks of lipid metabolism. It further dissects the role of lipid metabolism in reshaping the functions of T cells, B cells, macrophages, and dendritic cells, and delineates its organ-specific dysregulation in various ADs (e.g., synovium, skin, central nervous system, gut). Rather than blanket immunosuppression, we propose “immune-metabolic normalization”: titrating hyperactive nodes to physiological set-points while preserving host defense. We prioritize targets with high translational potential and evaluate corresponding targeted strategies, including drug repurposing, novel agents in clinical development, and innovative interventional concepts. Our work aims to bridge descriptive immunometabolic research with verifiable, patient-centered interventions, laying the groundwork for precision medicine in autoimmune diseases.